Ovarian Hyperstimulation Syndrome: A Narrative Review of Its Pathophysiology, Risk Factors, Prevention, Classification, and Management - Namavar Jahromi, Bahia (Iran J Med Sci, 2018)
Ovarian hyperstimulation syndrome (OHSS) is a serious complication of ovulation induction that usually occurs after gonadotropin stimulation, followed by human chorionic gonadotropin administration, for infertility treatment. The existing knowledge about the pathophysiology, risk factors, and primary and secondary methods for the prevention of OHSS is reviewed in this manuscript. The clinical manifestations and characteristics of mild, moderate, severe, and critical forms of the syndrome are defined. The methods of handling affected cases as outpatient or in-hospital management methods as well as indications for hospitalization are summarized in this review. The clinical and biochemical routes of assessing and monitoring hospitalized patients with OHSS, various drugs and medical treatment strategies including indications for aspiration of the ascitic fluid and pleural effusion, and also rare indications for surgery are briefly explained in this article. Severe OHSS, which two decades ago was considered an iatrogenic life-threatening condition, can now be effectively prevented or managed during the early stages. An OHSS-free clinic can be established nowadays by carefully considering the endocrinology of ovulation and using appropriate and dose-adjusted pharmaceutical agents, which are summarized and discussed in this review.